Midazolam microdose to determine systemic and pre-systemic metabolic CYP3A activity in humans - Hohmann, Nicolas; Kocheise, Franziska; Carls, Alexandra; Burhenne, Jürgen; Haefeli, Walter E.; Mikus, Gerd (British journal of clinical pharmacology, 2015)
Aim We aimed to establish a method to assess systemic and pre-systemic cytochrome P450 (CYP) 3A activity using ineffective microgram doses of midazolam. Methods In an open, one sequence, crossover study, 16 healthy participants received intravenous and oral midazolam at microgram (0.001 mg intravenous and 0.003 mg oral) and regular milligram (1 mg intravenous and 3 mg oral) doses to assess the linearity of plasma and urine pharmacokinetics. Results Dose-normalized AUC and Cmax were 37.1 ng ml−1 h [95% CI 35.5, 40.6] and 39.1 ng ml−1 [95% CI 30.4, 50.2] for the microdose and 39.0 ng ml−1 h [95% CI 36.1, 42.1] and 37.1 ng ml−1 [95% CI 26.9, 51.3] for the milligram dose. CLmet was 253 ml min−1 [95% CI 201, 318] vs. 278 ml min−1 [95% CI 248, 311] for intravenous doses and 1880 ml min−1 [95% CI 1590, 2230] vs. 2050 ml min−1 [95% CI 1720, 2450] for oral doses. Oral bioavailability of a midazolam microdose was 23.4% [95% CI 20.0, 27.3] vs. 20.9% [95% CI 17.1, 25.5] after the regular dose. Hepatic and gut extraction ratios for microgram doses were 0.44 [95% CI 0.39, 0.49] and 0.53 [95% CI 0.45, 0.63] and compared well with those for milligram doses (0.43 [95% CI 0.37, 0.49] and 0.61 [95% CI 0.53, 0.70]). Conclusion The pharmacokinetics of an intravenous midazolam microdose is linear to the applied regular doses and can be used to assess safely systemic CYP3A activity and, in combination with oral microdoses, pre-systemic CYP3A activity.